The mitochondrial regulator PGC1α is induced by cGMP–PKG signaling and mediates the protective effects of phosphodiesterase 5 inhibition in heart failure. Issue 1 (19th November 2021) - Zhu, Guangshuo; Ueda, Kazutaka; Hashimoto, Masaki; Zhang, Manling; Sasaki, Masayuki; Kariya, Taro; Sasaki, Hideyuki; Kaludercic, Nina; Lee, Dong‐ik; Bedja, Djahida; Gabrielson, Matthew; Yuan, Yuan; et al.
Abstract : Phosphodiesterase 5 inhibition (PDE5i) activates cGMP‐dependent protein kinase (PKG) and ameliorates heart failure; however, its impact on cardiac mitochondrial regulation has not been fully determined. Here, we investigated the role of the mitochondrial regulator peroxisome proliferator‐activated receptor γ co‐activator‐1α (PGC1α) in the PDE5i‐conferred cardioprotection, utilizing PGC1α null mice. In PGC1α +/+ hearts exposed to 7 weeks of pressure overload by transverse aortic constriction, chronic treatment with the PDE5 inhibitor sildenafil improved cardiac function and remodeling, with improved mitochondrial respiration and upregulation of PGC1α mRNA in the myocardium. By contrast, PDE5i‐elicited benefits were abrogated in PGC1α −/− hearts. In cultured cardiomyocytes, PKG overexpression induced PGC1α, while inhibition of the transcription factor CREB abrogated the PGC1α induction. Together, these results suggest that the PKG–PGC1α axis plays a pivotal role in the therapeutic efficacy of PDE5i in heart failure. Abstract : The phosphodiesterase 5 (PDE5) inhibitor sildenafil replenished myocardial expression of the mitochondrial regulator PGC1α, maintained mitochondrial ATP generating capacity and reduced oxidative stress, leading to the amelioration of maladaptive remodeling in later stages of heart failure during pressure overload. Neither the metabolic nor the physiological benefits of sildenafil treatment were observed in hearts lacking PGC1α. Our data provide evidence for the cardioprotection conferred by the cGMP‐PKG‐PGC1α axis upon PDE5 inhibition.